A Photoresponsive Stiff‐Stilbene Ligand Fuels the Reversible Unfolding of G‐Quadruplex DNA. Issue 13 (20th February 2019) - O'Hagan, Michael P.; Haldar, Susanta; Duchi, Marta; Oliver, Thomas A. A.; Mulholland, Adrian J.; Morales, Juan C.; Galan, M. Carmen
Abstract: The polymorphic nature of G‐quadruplex (G4) DNA structures points to a range of potential applications in nanodevices and an opportunity to control G4 in biological settings. Light is an attractive means for the regulation of oligonucleotide structure as it can be delivered with high spatiotemporal precision. However, surprisingly little attention has been devoted towards the development of ligands for G4 that allow photoregulation of G4 folding. We report a novel G4‐binding chemotype derived from stiff‐stilbene. Surprisingly however, whilst the ligand induces high stabilization in the potassium form of human telomeric DNA, it causes the unfolding of the same G4 sequence in sodium buffer. This effect can be reversed on demand by irradiation with 400 nm light through deactivation of the ligand by photo‐oxidation. By fuelling the system with the photolabile ligand, the conformation of G4 DNA was switched five times. Abstract : To fold or not to fold : A G‐quadruplex‐selective ligand derived from stiff‐stilbene strongly stabilises the potassium form of telomeric DNA, whilst causing the unfolding of the same sequence in sodium buffer. This effect can be reversed on demand by photoirradiation.